2019
DOI: 10.1002/cam4.2749
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted versus laparoscopic partial nephrectomy for anatomically complex T1b renal tumors with a RENAL nephrometry score ≥7: A propensity score‐based analysis

Abstract: Objectives:To present the perioperative, functional, and oncological outcomes of robot-assisted partial nephrectomy (RPN) compared with laparoscopic partial nephrectomy (LPN) for anatomically complex T1b renal tumors with RENAL nephrometry scores ≥7. Patients and methods: One hundred and seventy patients, during the study period, were retrospectively reviewed in our analysis according to inclusion criteria.Propensity score matching (PSM) (1:1) method was applied to impose restrictions on the potential baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 44 publications
2
20
0
1
Order By: Relevance
“…Seven studies were involved in our study [1,7,[11][12][13][14][15]. The literature searching process is summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies were involved in our study [1,7,[11][12][13][14][15]. The literature searching process is summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This could reach a quick renal function recovery. Instead, deng et al performed a study by propensity score-based analysis included 116 patients indicated that the eGFR decrease in baseline was similar between the two groups [11]. It could be deduced that RPN is favorable versus LPN in preserving renal function due to decreased WIT.…”
Section: Discussionmentioning
confidence: 99%
“…For a stage T1 renal tumor (RENAL nephrometry score ≥7) or renal tumor occurring in the isolated kidney, LPN could protect renal function better than LRN 14 . Due to the application of MR technology, surgeons could more comprehensively analyze renal tumor characteristics before surgery and could more accurately locate renal tumors during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: (I) all patients underwent renal contrast‐enhanced CT scanning; (II) all patients had a stage T1 renal tumor; (III) all renal tumors had a RENAL nephrometry score 14 ≥7; (IV) all operations were performed by two senior surgeons; and (V) surgical records of the presence and area of APF were available. The exclusion criteria were as follows: (I) CT contrast agent allergy; (II) severe cardiovascular and cerebrovascular diseases; (III) severe kidney dysfunction; and (IV) severe renal artery stenosis or occlusion.…”
Section: Methodsmentioning
confidence: 99%
“…Сьогодні вже зрозуміло, що використання селективної емболізації гілок ниркової артерії, що живить зону ймовірної резекції на передопераційному етапі, є доцільним, при цьому не потрібна інтраопераційна дисекція судин нирки, значно зменшується можливість травми судин, рівень крововтрати, покращується візуалізація операційного поля, кордонів "здорової" паренхіми та пухлини, стає недоцільним використання гемостатичних швів із захопленням значної частини паренхіми нирки, що у подальшому має негативне значення та спричиняє розвиток зниження функції оперованої нирки та розвиток нефросклерозу [36,37]. З урахуванням отриманих багатьма дослідженнями даних сьогодні алгоритм лікування хворих на рак нирки насамперед спрямований на мінімізацію обсягу вилученої частини органа і відповідно підвищення "функціональності" виконуваного хірургічного втручання [38,39,40].…”
unclassified